Cellular and circuit diversity determines the impact of endogenous opioids in the descending pain modulatory pathway - McPherson, Kylie B.; Ingram, Susan L. (Frontiers in Systems Neuroscience, 2022)
The descending pain modulatory pathway exerts important bidirectional control of nociceptive inputs to dampen and/or facilitate the perception of pain. The ventrolateral periaqueductal gray (vlPAG) integrates inputs from many regions associated with the processing of nociceptive, cognitive, and affective components of pain perception, and is a key brain area for opioid action. Opioid receptors are expressed on a subset of vlPAG neurons, as well as on both GABAergic and glutamatergic presynaptic terminals that impinge on vlPAG neurons. Microinjection of opioids into the vlPAG produces analgesia and microinjection of the opioid receptor antagonist naloxone blocks stimulation-mediated analgesia, highlighting the role of endogenous opioid release within this region in the modulation of nociception. Endogenous opioid effects within the vlPAG are complex and likely dependent on specific neuronal circuits activated by acute and chronic pain stimuli. This review is focused on the cellular heterogeneity within vlPAG circuits and highlights gaps in our understanding of endogenous opioid regulation of the descending pain modulatory circuits.